2022
DOI: 10.3389/froh.2022.871033
|View full text |Cite
|
Sign up to set email alerts
|

Transparency of COVID-19-Related Research in Dental Journals

Abstract: ObjectiveWe aimed to assess the adherence to transparency practices (data availability, code availability, statements of protocol registration and conflicts of interest and funding disclosures) and FAIRness (Findable, Accessible, Interoperable, and Reusable) of shared data from open access COVID-19-related articles published in dental journals available from the Europe PubMed Central (PMC) database.MethodsWe searched and exported all COVID-19-related open-access articles from PubMed-indexed dental journals ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…On the other hand, a recent study of 200 articles showed that adherence to COI and funding disclosures improved from preprints to peerreviewed publications and showed higher adherence to funding disclosures than our findings indicated [28]. In addition, adherence to transparency practices was higher than in our previous study on COVID-19-related research in dental journals [21].…”
Section: Plos Onecontrasting
confidence: 91%
“…On the other hand, a recent study of 200 articles showed that adherence to COI and funding disclosures improved from preprints to peerreviewed publications and showed higher adherence to funding disclosures than our findings indicated [28]. In addition, adherence to transparency practices was higher than in our previous study on COVID-19-related research in dental journals [21].…”
Section: Plos Onecontrasting
confidence: 91%
“…However, compared with coronavirus disease 2019 (COVID-19)-related dental research analyzed using the same methods [22], our findings showed higher adherence to all transparency practices. For instance, much higher adherence to COI disclosure was observed in all dental research (86%-95%, Supplementary Material at osf.io/4eq8u) than in COVID-19-related dental research (74%) during the period 2020-2021 [22]. A comparison with almost three million biomedical research articles analyzed using the same automated tools as the present study showed that COI disclosures were included more often in dental research articles than in biomedical articles in 2020 [4].…”
Section: Discussionmentioning
confidence: 57%
“…Thus, there were deficiencies in some of the five aspects of transparency in almost all articles. However, compared with coronavirus disease 2019 (COVID‐19)‐related dental research analyzed using the same methods [ 22 ], our findings showed higher adherence to all transparency practices. For instance, much higher adherence to COI disclosure was observed in all dental research (86%–95%, Supplementary Material at osf.io/4eq8u) than in COVID‐19‐related dental research (74%) during the period 2020–2021 [ 22 ].…”
Section: Discussionmentioning
confidence: 83%
“…Only one study, representing 0.15%, shared raw data, and none provided access to their code. Articles published in journals with higher impact factors, as well as those published in 2020, demonstrated a greater tendency towards transparency compared to those in 2021 [ 15 ]. Another transparency assessment was performed in orthopedic literature [ 16 ].…”
Section: Discussionmentioning
confidence: 99%